Penyuluhan Tempat Perindukan Alami Nyamuk Aedes aegypti Vektor DBD di Dusun Pal 6, Kabupaten Lampung Selatan - Yulianti; Endang Nurcahyani; Endang Linirin; Selvi Marcelia; Linda Septiani; Emantis Rosa (CV. Multi Kreasi Media, 2023)
The breeding places that are known to the public are still limited to the breeding places that are inside the house, even though there are still many breeding places outside, such as plants that can accommodate stagnant water which are used by mosquitoes as breeding places, are still not widely known by the public. The purpose of this community service activity is to introduce and increase public knowledge of mosquito breeding places as an effort to control DHF vector insects in order to reduce DHF cases in the community. The results of the activity showed that there was an increase in public knowledge about the natural breeding places for the DHF vector by 34.83% of (46.30% - 81.13%).